Development of decentralized apps using blockchain technology to improve Malaysian government services in Ministries of Home Affairs – digital identity management - Pang, Yi Wern (2022)
In this project, it proposes the development of decentralized identity management system using Blockchain technology. This proposed project focuses on improving Malaysia government services in Ministries of Home Affairs in terms of better safeguarding and managing user’s identity claims or documents. Nowadays, whether the way of identification is through physical or digital, there are still some challenges during the management process that exist both physically and electronically. Problems faced by existing identity management system including risks of data breaches, abuse of trust issues and over-relying on middleperson. This shows that security, trust, and convenience are important factors to make the identification process tamper resistant, trustable and cost and time effective. The emergence of blockchain distributed ledger technology is having the potential to enhance transparency, trust in record keeping, user control in transactions that involve identity information and decentralization in identity management. It is having a bright future in the upcoming years and has been increasingly used and improved up till now. The characteristics like transparency, trust and tamper resistant has revolutionized different aspects including business, government and political interactions, social and any other value exchanging mechanisms. Blockchain ensures that governmental procedures and business transactions are highly secured, trustable, effective, and efficient. Therefore, Blockchain technology is selected to improve Malaysia government services in terms of identity management. The scope of the project will be log-in interface to control access of different roles, verification procedure to ensure validity of user’s registered claims, user and government are connected in one system, and user having self-sovereign identity. This project has also reviewed other existing blockchain identity management system in order to evaluate the strengths and weakness of other systems and apply those strengths and improve the weakness through my proposed project. The methodology used in this project is prototyping-based methodology, which is under the rapid application development (RAD) methodology category. The tools or technologies involved in the project are visual studio code for the web application development, Metamask extension on web browser for the Ethereum tesnetconnection and Infura service public API that offers the ability to get access to a node that is hosted on the Rinkeby network. There are three main roles in the proposed blockchain identity management system which are user, issuing authority and service provider. All three roles are connected in one system. Users can register and manage their identity claims by having self-sovereign identity. Issuing authority will be responsible in verifying user’s registered identity claims to prove the validity of the claims. While for service provider, before accessing user’s identity claims, they are required to send access request to users for their approval to access their claims. Metamask accounts are required to logged-in to allow all process of the system work effectively. In conclusion, at the end of the project, the proposed system will be able to solve all problems stated in existing identity management system which are risks of data breaches and identity thefts, abuse of trust issues that results in lack of trust in business parties and over-relying on middle person issue.